2006
DOI: 10.1007/s10620-006-3211-2
|View full text |Cite
|
Sign up to set email alerts
|

A Decrease in AFP Level Related to Administration of Interferon in Patients with Chronic Hepatitis C and a High Level of AFP

Abstract: It is known that there is a very high incidence of hepatocellular carcinoma (HCC) among patients with type C chronic hepatitis and cirrhosis, and alpha -fetoprotein (AFP) has been widely used as a diagnostic marker for HCC. However, there are some patients showing continuous high AFP values but no evidence of HCC, and some studies have defined such patients as a high-risk group for HCC. In vitro study has shown that interferon (IFN) inhibits cell proliferation and enhances apoptosis as well as specific cytotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 17 publications
3
40
0
Order By: Relevance
“…Until now, it has been recognized that only low-dose long-term interferon injection can improve serum AFP levels 11 . Since a high level of AFP is suggested to be one of the major risk factors of the development of HCC 12,13 , lowering serum AFP levels is important to prevent HCV-related hepatocarcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, it has been recognized that only low-dose long-term interferon injection can improve serum AFP levels 11 . Since a high level of AFP is suggested to be one of the major risk factors of the development of HCC 12,13 , lowering serum AFP levels is important to prevent HCV-related hepatocarcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…For the high-risk group, ultrasound and tumor-marker measurements are recommended every 6 months. Addition of DCP or AFP-L3 is considered necessary because these are diagnostic markers whereas AFP is a marker of risk (129,130 ). Detection of a nodular lesion by ultrasound and/or a continuous rise in AFP (Ͼ200 g/L), DCP [in arbitrary units (AU) with 1 AU ϭ 1 g prothrombin] (Ͼ40 mAU/mL), or AFP-L3 (Ͼ15%) requires further evaluation by dynamic CT or MRI (127,128 ).…”
Section: (512-515 )mentioning
confidence: 99%
“…In addition, there are case reports that IFN therapy reduced AFP levels in virological nonresponders [49]. Murashima et al [50] showed that IFN therapy, but not Strong NeoMinophagen C (SNMC) (Glycyrrhizin, Tokyo, Japan), universally reduced basic AFP levels. In an in vitro study of the effects of IFN on an HCC cell line, IFN exhibited antitumor effects [51].…”
Section: Development Of Hccmentioning
confidence: 99%